ChemInform Abstract: Characterization and Quality Control of Pharmaceutical Cocrystals. Issue 47 (3rd November 2016) - Izutsu, Ken‐ichi; Koide, Tatsuo; Takata, Noriyuki; Ikeda, Yukihiro; Ono, Makoto; Inoue, Motoki; Fukami, Toshiro; Yonemochi, Etsuo
Abstract: Review: 106 refs.